Reducing delays in the diagnosis and treatment of muscle-invasive bladder cancer using simulation modelling. (March 2019) - Chalk, Daniel; Trent, Neil; Vennam, Sarath; McGrane, John; Mantle, Mark
Objective: To develop a simulation model to identify key bottlenecks in the bladder cancer pathway at Royal Cornwall Hospital and predict the impact of potential changes to reduce these delays. Materials and methods: The diagnosis and treatment of muscle-invasive bladder cancer can suffer numerous delays, which can significantly affect patient outcomes. We developed a discrete event computer simulation model of the flow of patients through the bladder cancer pathway at the hospital, using anonymised patient records from 2014 and 2015. The changes tested in the model were for patients suspected to have muscle-invasive disease on flexible cystoscopy. Those patients were 'fast-tracked' to receive their transurethral resection of bladder tumour (TURBT) treatment using operating slots kept free for these patients. A staging computed tomography scan was booked in the haematuria clinic. Pathology requests were marked as 48 hour turnaround. The nurse specialist would then speak to the patient whilst they were on the ward following their TURBT to give information about their ongoing treatment and provide support. Results: The model predicted that if the changes were implemented, delays in the system could be reduced by around 5 weeks. The changes were implemented, and analysis of 3 months of the data post-implementation shows that the average time in the system was reduced by 5 weeks. The environment created by the changes in the pathway improved referral to treatment times in both muscle-invasive and non-muscle-invasive groups. Conclusion: The simulation model proved an invaluable tool for facilitating the implementation of changes. Simple changes to the pathway led to significant reductions in delays for bladder cancer patients at Royal Cornwall Hospital. Level of evidence: Not applicable for this cohort study.